Processes of Spatialization in the Americas Configurations and Narratives - Pisarz-Ramirez, Gabriele; Warnecke-Berger, Hannes (Interamericana, 2018)
Where do the Americas begin, and where do they end? What is the relationship between the spatial constructions of «area» and «continent»? How were the Americas imagined by different actors in different historical periods, and how were these imaginations - as continent, nation, region - guided by changing agendas and priorities? This interdisciplinary volume addresses competing and conflicting configurations and narratives of spatialization in the context of globalization processes from the 19th century to the present.